Meeting the nutrition and physical activity needs of young people in residential out-of-home care. (March 2023) - Green (nee Cox), Rachael; Savaglio, Melissa; Bruce, Lauren; Tate, Ruby; Hatzikiriakidis, Kostas; Smales, Madelaine; Crawford-Parker, Anna; Marshall, Sandra; Graham, Veronica; Skouteris, Helen
Summary: Health outcomes for young people living in residential out-of-home care are poor. There has been increased emphasis on the need to prioritize preventative support and upskill residential care workers to better meet young people's health needs. The aim of this study was to examine the food quality and physical activity environment in residential care houses in Victoria, Australia prior to staff undertaking Healthy Eating, Active Living Matters (HEAL) training; 102 residential care houses participated. House representatives completed an online survey exploring: (1) physical activity equipment and engagement and (2) weekly food budget and expenditure. Findings: The average weekly food expenditure per household was $318.98 (SD = $106.51), with variation between different sized households. The majority (61%) of houses' weekly food expenditure was spent on ultra-processed food products that are ready to eat with no/little preparation, in comparison to 36% spent on unprocessed foods (fresh fruit and vegetables). The majority of houses reported having two types of equipment. Young people were not often engaged in physical and/or recreational activities in their community. Application: Residential care houses in Victoria require additional supports to ensure that young people are supported to eat well and be active at home and in the community. HEALing Matters aims to provide this, by offering professional development for residential carers to better facilitate engagement in physical activity and healthy eating among the young people in their care. If successful, HEALing Matters may provide an effective pathway to improved health and wellbeing outcomes for young people in residential care.